Manfaat Penerapan Sistem Informasi Akuntansi Terhadap Kualitas Laporan Keuangan Bank Jatim Syariah Cabang Jember - Sunardi Sunardi; Nihayatut Tasliyah; Khalidatus Sa’adah (Program Studi Akuntansi Syari'ah Universitas Ibrahimy, 2023)
The rapid development of information technology and computers. Encouraging companies to utilize ICT to support their business operations. Starting from planning, managing, controlling, evaluating, and presenting data and information to support decision-making activities. One of them is Bank Jatim Syariah through the implementation of an Accounting Information System called ESTIM. This system has the main function of managing all financial transactions and company financial reports online, real-time, and according to standards set by Bank Indonesia and the Financial Services Authority. This study aims to determine the benefits of implementing the SIA on the quality of financial reports. This qualitative descriptive research was conducted at the office of the Bank Jatim Syariah Jember Branch, with data sources from parties involved with the bank's AIS as primary data. The data was obtained through interviews and documentation. Then it is processed using qualitative data analysis method and its validity is tested by triangulation. The results of the study concluded that the implementation of the ESTIM system, as an accounting information system for Bank Jatim Syariah, provides many benefits for companies, especially in the aspects of online and realtime data storage and access, and is able to improve the quality of Bank Jatim Syariah financial reports to Bank Indonesia. Namely by presenting financial reports that are systematic, complete, accurate, fast, and have characteristics as reports that are reliable, relevant, understandable and comparable.